ANALISIS SISTEM PENJUALAN DAN PENERIMAAN KAS UNTUK MENINGKATKAN PENGENDALIAN INTERN PERUSAHAAN CV ANUGERAH BAMBA CASALLE SURABAYA: (Studi Kasus Pada CV.Anugerah Bamba Casalle Surabaya) - Deviana Pertiwi; Hendra Dwi Prasetyo (Ekomania, 2023)
The purpose of this research is to study the procedures and systems of collecting and selling money and to help CV Anugerah Bamba Casale improve internal control. This survey is a descriptive survey using a qualitative approach. Data obtained from secondary data. Documentary data collection method. Data analysis includes aspects of the sales and billing system and procedures of CV Anugerah Bamba Casalle, as well as internal control. The results showed that the finance and purchasing functions were combined, the tax function was not included in the organizational structure, and the implementation of sales activities was not carried out by other functions or integrated into the company's department. There is a management function as well as a cashier function.